Enhancement of Early Childhood Education (ECE) through Professional Development: Sri Lankan ECE Teachers’ Perceptions - Abeywickrama, Rohan (English Department, Faculty of Humanities, Andalas University, 2024)
This study examined the influence of teacher Professional Development onthe quality of learners’ cognitive development, behavior management, andthe overall effectiveness of Early Childhood Education. A questionnairewas administered among 285 Early Childhood Education (ECE) teachersserving at private educational institutions in Sri Lanka to gather data. Thestratified sampling method was applied to select the respondents and thefindings were analyzed using descriptive statistics, reliability analysis,correlation, and regression analysis. The study results demonstratethat teacher Professional Development has a positive and significantimpact on the quality of the ECE classroom, young learners’ cognitivedevelopment, behavior management, and the overall effectiveness ofthe ECE. The current study provides important insights into the role ofteacher Professional Development in enhancing the quality of ECE inSri Lanka. The study underscores the critical significance of ProfessionalDevelopment in reinforcing the quality of ECE in Sri Lanka. It advocatesfor continuous investment in teacher Professional Development initiatives,recognizing their potential to raise the standards of ECE classrooms, fostercognitive development among young learners, and facilitate positivebehavior management techniques. Furthermore, the research emphasizesthe necessity for future investigations to explore deeper into the correlationbetween teacher Professional Development and the efficacy of ECE. Suchinquiries could uncover insights and explain strategies aimed at optimizingthe effectiveness of ECE across diverse contexts.